Inhibition of Hepatitis B Virus by AAV8-Derived CRISPR/SaCas9 Expressed From Liver-Specific Promoters - Yan, Kun; Feng, Jiangpeng; Liu, Xing; Wang, Hongyun; Li, Qiaohong; Li, Jiali; Xu, Tianmo; Sajid, Muhammad; Ullah, Hafiz; Zhou, Li; Zhou, Limin; Chen, Yu (Frontiers in Microbiology, 2021)
Curative therapies for chronic hepatitis B virus (HBV) infection remain a distant goal, and the persistence of stable covalently closed circular DNA (cccDNA) during HBV replication is a key barrier that is hard to break through using the drugs currently approved for HBV treatment. Due to the accuracy, efficiency, and cost-effectiveness of genome editing, CRISPR/Cas technologies are being widely used for gene therapy and in antiviral strategies. Although CRISPR/Cas could possibly clear cccDNA, ensuring its safety is requirement for application. In our study, we analyzed the liver specificity of several promoters and constructed candidate promoters in the CRISPR/Staphylococcus aureus Cas9 (SaCas9) system combined with hepatotropic AAV8 (whereby AAV refers to adeno-associated virus) to verify the efficacy against HBV. The results revealed that the reconstructed CRISPR/SaCas9 system in which the original promoter replaced with a liver-specific promoter could still inhibit HBV replication both in vitro and in vivo. Three functional guide RNAs (gRNAs), T2, T3, and T6, which target the conserved regions of different HBV genotypes, demonstrated consistently better anti-HBV effects with different liver-specific promoters. Moreover, the three gRNAs inhibited the replication of HBV genotypes A, B, and C to varying degrees. Under the action of the EnhII-Pa1AT promoter and AAV8, the expression of SaCas9 was further decreased in other organs or tissues in comparison to liver. These results are helpful for clinical applications in liver by ensuring the effects of the CRISPR/Cas9 system remain restricted to liver and, thereby, reducing the probability of undesired and harmful effects through nonspecific targeting in other organs.